Star taker: art, science and mathematics in an astrolabe from fourteenth-century Spain. Issue 2 (3rd July 2018) - Bentley, Patricia
ABSTRACT: The astronomical instrument known as the astrolabe has been called star taker, mirror of the sun, and recently, the first personal computer. First developed by the ancient Greeks, it was refined and improved by scientists working in medieval Islamic lands. Studying it reveals the many ways in which art, science and mathematics were employed in its making and its use. It is a product of all three disciplines: it works through stereographic projection, making trigonometric calculations possible. By rotating the movable parts that indicate the relative positions of heavenly bodies, the user can determine exact times and distances on earth. It is also an example of the fine art of metalworking. The essay explores the astrolabe's functioning and significance with a particular focus on a fourteenth-century astrolabe in the Aga Khan Museum collection in Toronto. Its potential for use in museum education is examined, with suggestions for in-gallery interpretive strategies. GRAPHICAL ABSTRACT: